Role of Active Methods in the Teaching Process Intensification during Training of International Relations Specialists - Tarasova, Olha (Pedagogical Discourse, 2011)
Methods and forms of the teaching process intensification are viewed in the article. Also the role of these methods during training of international relations specialists in Ukraine and abroad is determined.